PENGEMBANGAN MEDIA MONOPOLI DALAM PEMBELAJARAN SENI BUDAYA UNNTUK SISWA KELAS IV SEKOLAH DASAR - Reski Dwi Yuliana, Andi; Ahmad Syawaluddin; Bhakti Prima Findiga Hermuttaqien (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the limited availability of learning media for Cultural Arts, resulting in insufficient understanding among fourth-grade students, as well as the need for differentiated learning to accommodate student diversity. The study aimed to develop and assess the feasibility of a Monopoly media using the Research and Development (R&D) ADDIE model, which was implemented among fourth-grade students at UPTD SDN 48 Barru. The analysis phase involved teacher interviews, followed by planning the media design and instruments. The development stage included media production, validation by material and media experts, and revisions until the product reached the "Very Good" category. The media was then tested on small and large groups. Questionnaire data were analyzed descriptively using percentages, revealing "Very Feasible" responses from both students and teachers. Formative evaluations were conducted at each stage to refine the product. Based on the development process and assessment results—which identified student needs and learning challenges, while the design emphasized clear objectives and engaging content structure—the feasibility of the Monopoly media for Cultural Arts, observed through validation and student trials, showed a validation score of 52% (Good category) and a student response rate of 82%. It can be concluded that the Monopoly media is feasible for use in Cultural Arts learning for fourth-grade elementary students.